DINAMIKA KELOMPOK PERKUMPULAN PETANI PEMAKAI AIR DI LAHAN RAWA LEBAK - Yanti Rina D (Sepa, 2017)
Water management is the success key  to successful farming in  swampland. The existence of water management institutions such as the  Water Users Asociation (WUA)  in  swampland  generally  has  not  been  independent.  To  determine  the performance of group dynamics and its relation to the level of leadership behavior of the group leader and effectiveness of  WUA  groups in lowland swamp, then research carried out with survey method in 2013. Sample groups are purposively determined as many as 8 units WUA  group comprising: 4 (four) P3A groups in Hulu Sungai Selatan and 4 units in the district Hulu Sungai Utara on South Kalimantan Province. Samples farmers  randomly  selected  120  people.  Primary  data  were  collected  through interviews using structured questionnaire. Data were analyzed descriptively and using Spearman's  Rank  correlation  analysis.  The  results  showed  WUA  group  dynamics, leadership  behavior  of  WUA  group  and  effectiveness  of  WUA  group  in  medium category. The good of WUA group leadership behaviors can improve group dynamics, further, the dynamic group  WUA increase the effectiveness of the group. The increase in group dynamics can be done through guidance on the creation of an atmosphere conducive group, reducing the pressure groups, the development and maintenance of  the group and to improve the function of the task WUA group.